Kewenangan Penjabat Negeri Dalam Pengangkatan Dan Pemberhentian Saniri Negeri Laha Kaba Kecamatan Telutih Kabupaten Maluku Tengah - Koranelao, Abdul Latif; Nendissa, Renny Heronia; Soplanit, Miracle (PATTIMURA Law Study Review, 2023)
State officials took arbitrary actions in appointing and dismissing Saniri without any deliberation from each clan or soa which had the right and authority to appoint and dismiss State Saniri Central Maluku Regency Regional Regulation No. 04 of 2006 concerning Guidelines for Structuring State Saniri/Village Consultative Bodies explains in Article 19 Point 1 "State Saniri are selected based on representation in accordance with local customs, customary law and culture." This writing discusses two issues, namely: 1) Do State Officials have the authority to appoint and dismiss State Saniri in accordance with statutory regulations. 2) What are the legal consequences of Saniri's appointment by a State Official? The purpose of this research is to examine and analyze the authority of State Officials in appointing and dismissing State Saniri and the Legal Consequences of Appointing Saniri by State Officials. The method used in this research is a normative legal research method. The results of this research indicate that the delivery and dismissal of State Saniri by State Officials is not in accordance with local state customs or is contrary to statutory regulations. The Decree of the Regent of Central Maluku regarding the Appointment of State Saniri is invalid or legally flawed.